A Personal Approach to Syllabus Design: A Blueprint for Learning in Composition Class - Poudel , Prativa (Journal of NELTA, 2025)
This article explains the thinking behind my English 102 syllabus design and the choices I made to help students become better writers. I recently surveyed a cohort of undergraduate students on what they would like me to include in the syllabus and how I should teach and guide them in the class to meet their needs. Considering most of their ideas and concerns, I designed this syllabus to be more student-friendly by making it more welcoming and accessible to promote active student participation in my classroom. This syllabus focuses on flexibility and a student-centered approach adapting diverse learning styles. This article also discusses why I encouraged language diversity in students’ writing, what the insights are behind preparing the assignments, and how the grading mechanisms I follow will provide clarity and fairness to the students. By highlighting creative expression and prioritizing critical thinking over perfect grammar, this research also encourages the various ways people communicate their thoughts, feelings, ideas, and creativity using multimodal technology to reflect modern communication practices as well. The essay is not simply about the syllabus but also my learning process as I developed it to show reflection and growth. The course centers on the interdisciplinary theme of Animal Studies, linking writing to real-world contexts to encourage critical thinking across subjects. By contrasting this approach with more rigid curricula in Nepal, I highlight the value of teacher autonomy and flexible design in supporting student learning. This article contributes to conversations about inclusive and responsive pedagogy.